Pembuatan Kopi dari Kulit Pisang Kepok (Musa paradisiaca Linn) dan Aktivitas Antioksidannya - Allikha Bias Mentari; Siti Nur Kholisoh; Taufik Nor Hidayat; Umar Hafidz Asy'ari Hasbullah (Jurnal Ilmu Pangan dan Hasil Pertanian, 2019)
Processing coffee from kepok banana peel is an option in diversifying food preparations and providing non-caffeine coffee. This study aims to study the characteristics of banana peel coffee based on fruit maturity and oven duration. In addition, it also analyzes total phenol and its antioxidant activity. The study design used a factorial randomized design with the first factor of fruit maturity (unripe and ripe) and the second factor of oven length (5, 10, and 15 minutes). Banana skin coffee has a yield ranging from 8.6 to 11.6%. Bulk density ranges from 0.43-0.48g/ml. Water content ranges from 3.9-6.39%. Ash content ranges from 0.92-6.79%. The content of phenol ranges from 0.6 to 2.46 mg PE/g. The coffee phenol content of ripe banana peel is larger than unripe. The longer oven increases the phenol content. IC50 and EC50 decrease with increasing phenol. The antioxidant activity of ripe banana peel coffee is larger than unripe